Critical Discourse Analysis, Description, Explanation, Causes: Foucault's Inspiration Versus Weber's Perspiration - Wickham, Gary; Kendall, Gavin (Forum Qualitative Sozialforschung / Forum: Qualitative Social Research, 2007)
The FOUCAULTian governmentality approach, in relying on a teleology—the ultimate purpose of human endeavour is the quest for ever-growing human reason, a reason that is the universal basis of moral judgements, especially moral judgements about political and legal actions—leads not to description, explanation and the possible identification of causes, but to critique, to the inappropriate conflation of, on the one hand, description, explanation and the identification of causes with, on the other, political criticisms sourced in the teleology. Drawing on some of WEBER's methodological insights, an argument is developed that critical discourse analysis, in taking on the FOUCAULTian approach, gives up the best traditions of description, explanation and the identification of causes in favour of the expression, in many different forms, of the teleology.URN: urn:nbn:de:0114-fqs070246